Benchmarking public school performance by unionized status. Issue 7 (3rd October 2016) - Overton, Kathleen; Joo, Seong-Jong; Stoeberl, Philipp A.
Abstract : Purpose: There are elevated debates on the role of teacher unions on the effectiveness of education in the USA. The purpose of this paper is to examine if the unionization of education has an impact on the comparative performance of public education in the USA. Design/methodology/approach: The authors classify states into two groups such as highly unionized states and less unionized states for comparing their performance differences. The analyses consist of two stages. First, the authors apply data envelopment analysis (DEA) to the key performance indicators of the groups. Next, the authors use statistical analysis for confirming the statistical significance of the performance differences that may exist between two groups. Findings: The authors have confirmed the adverse impact of unionization on public education using DEA models and non-parametric rank-sum tests. However, the authors are cautious for generalizing the finding due to the limitations described in the research limitation section. Research limitations/implications: The finding is limited within the selection of the variables and model specification and requires additional studies using different variables and models. The authors hope that the study motivates researchers to conduct further studies in this area. Originality/value: Major contributions of the study include a novel approach for measuring the performance of primary and secondary schools at the state level by classifying and choosing less or highly unionized states and suggesting insights for improvements.